Legal Challenges in Managing Intellectual Property Rights in Business Information Systems - Elpina Elpina (Jurnal Minfo Polgan, 2024)
With the advancement of information technology, business information systems have become integral elements in business operations across various sectors. However, the use of this technology also brings new challenges in managing intellectual property rights, including the protection of copyrights, patents, trademarks, and others. This research aims to analyze the legal challenges in managing intellectual property rights in business information systems through the perspective of Law No. 11 of 2008 concerning Electronic Information and Transactions in Indonesia. The method used in this research is a qualitative literature review, drawing data from Google Scholar for the period from 2009 to 2024. The qualitative approach in the literature review allows researchers to understand the complex and diverse phenomena related to the research topic. The results of the study indicate that the management of intellectual property rights (IPR) in business information systems in Indonesia faces complex legal challenges. Although Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law) provides a framework, its implementation often leads to uncertainty and challenges in IPR protection. One of the main challenges is the clarity and legal certainty in the digital environment, as well as consistent law enforcement against IPR violations. Thus, there is a need to enhance cooperation between the government, law enforcement agencies, and the private sector to improve law enforcement related to IPR in business information systems.